Evolved birth physiology meets modern birth practice: Sustained effects of planned cesarean delivery on child hair cortisol in Brazil - Zaneta M. Thayer; Romina Buffarini; Luciana Tovo-Rodrigues; Isabel Oliveira de Oliveira; Pedro C. Hallal; Luisa M. Rivera; Mariângela Freitas Silveira (Proceedings of the National Academy of Sciences, 2025)
Cesarean section (CS) is the most common major surgery worldwide and, by enabling birth outside physiologic labor, is an evolutionary novelty. Labor-related mechanical and hormonal stimuli, shaped by natural selection, facilitate neonatal adaptation to extrauterine life. While prior work has emphasized the biological impacts of altered microbial exposure following CS, the developmental implications of missing labor are less explored. We evaluated whether birth without labor was associated with differences in child hair cortisol, an integrated measure of hypothalamic–pituitary–adrenal activity that influences growth, metabolism, immunity, and behavior. Using longitudinal data from singleton births in the 2015 Pelotas Birth Cohort in Brazil ( N = 6 , 136 observations from 3,537 participants), we found that 4 to 7 y old children born through planned CS before labor had 6.6% lower hair cortisol than children born vaginally ( P = 0.002 ) and 4.4% lower cortisol than children born from unplanned CS after labor ( P = 0.017 ). There were no significant differences in hair cortisol levels between children born vaginally and through CS after labor, suggesting that labor exposure, rather than CS delivery, is associated with the observed differences. A significant interaction between labor experience and gestational age indicated that differences were most pronounced among children born without labor at earlier gestational ages; adjusted differences between planned CS and vaginal delivery were significant before 39.5 wk gestation. These findings support the hypothesis that labor is an evolved developmental exposure and that bypassing it may have unintended biological consequences.